Effectual Outworking of Environmental Sustainability, Energy Security and Energy Equity in the Energy Consumption, Economic Growth and Emission Reduction in the ASEAN - Recto, King Harold A (Archīum Ateneo, 2022)
With the pandemic coming to an end, the world is expected to revert to most, if not all, of its economic activities prior to the pandemic to ensure economic recovery. However, this pursuit also impacts energy consumption, economic growth, and emission reduction. There have been several studies that have tackled this but only on a macro-scale and were focused on developed countries, so the context is different from Southeast Asia. Using regression modelling of World Energy Council (WEC) trilemma scores of the member countries of the Association of Southeast Asian Nations (ASEAN), its mathematical relationships with energy consumption, economic growth and emission reduction were determined, as well as its implications to sustainable energy policy in the ASEAN. The study found out that Gaussian Process Regression – Exponential GPR is the best fit model to use for this purpose. Considering the findings, policies to (1) encourage investments in clean energy, (2) push for clean energy transition, (3) reduce energy-related carbon dioxide emissions, (4) study the differences in energy use and efficiency across groups and (5) advocate energy savings were forwarded.